Numerical Study on Combustion Behavior of Tuyere and Raceway in Blast Furnace with Oxygen-Rich Blast and Hydrogen Injection - Ruimeng Shi; Yue Pei; Mengmeng Ren; Zheng Xue; Xinqi Li; Heping Liu (Metals)
The injection of hydrogen into a blast furnace is a promising technology to fulfill the low-carbon ironmaking purpose. A three-dimensional computational fluid dynamic (CFD) model is developed to investigate the effect of hydrogen injection rate and blast oxygen enrichment rate on the tuyere, raceway, and surrounding coke bed behaviors. It was found that hydrogen injection leads to a higher water vapor volume fraction in the raceway and a higher hydrogen fraction in the coke bed. The magnitude of velocity and temperature near the tuyere only increase slightly due to the cold inlet temperature of hydrogen, which also results in lower coke bed temperature. The volume-averaged temperature decreases from 2146 K to 2129 K when the injection rate increases from 0 to 1000 Nm3/h. Oxygen enrichment rate presents a highly positive correlation with temperature in the raceway and coke bed, water vapor and carbon dioxide volume fraction in the raceway, and pulverized coal burnout rate. Because more carbon participates in the raceway reaction with an increase in oxygen enrichment rate from 0% to 10%, the final carbon monoxide fraction in the coke bed increases from 0.29 to 0.40, and the final hydrogen fraction decreases from 0.15 to 0.13. With the increase in hydrogen injection, the temperature of the raceway and the coke bed decreased slightly. Pulverized coal burnout changes little with the hydrogen injection rate increasing from 500 Nm3/h to 1500 Nm3/h, which is because hydrogen combustion promotes pulverized coal at the front part of the raceway but inhibits it at the end due to the relative lack of oxygen. These results will help better understand the combustion behavior in the tuyere and raceway of the blast furnace with oxygen-rich blast and hydrogen injection.